The Relationship Between Gender and Emotional Eating in Adolescents - Piloto, Thesya Claudya Putri; Nugraheni, Fitriana (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Adolescence, a period filled with pressure, can influence eating behaviors, including the tendency toward emotional eating. One of the factors contributing to this behavior is gender. This study aims to explore the relationship between gender and emotional eating among adolescents at SMAN 5 Surabaya. The research employs a quantitative method with a cross-sectional design, involving 142 respondents selected through cluster random sampling. Data were collected using the Salzburg Emotional Eating Scale (SEES) questionnaire and analyzed using the Chi-square test. The results indicate a significant relationship between gender and emotional eating (p = 0,007), with males exhibiting a higher tendency for emotional eating than females. These findings are expected to serve as a foundation for more targeted interventions in addressing emotional eating among adolescents while considering gender factors.